A nationwide follow-up study of occupational organic dust exposure and risk of chronic obstructive pulmonary disease (COPD). Issue 2 (31st December 2018) - Vested, Anne; Basinas, Ioannis; Burdorf, Alex; Elholm, Grethe; Heederik, Dick J J; Jacobsen, Gitte H; Kolstad, Henrik A; Kromhout, Hans; Omland, Øyvind; Sigsgaard, Torben; Thulstrup, Ane M; Toft, Gunnar; et al.
Abstract : Objectives: To study exposure-response relations between cumulative organic dust exposure and incident chronic obstructive pulmonary disease (COPD) among subjects employed in the Danish farming and wood industry. Methods: We studied exposure-response relations between cumulative organic dust exposure and incident COPD (1997–2013) among individuals born during 1950–1977 in Denmark ever employed in the farming or wood industry (n=1 75 409). Industry-specific employment history (1964–2007), combined with time-dependent farming and wood industry-specific exposure matrices defined cumulative exposure. We used logistic regression analysis with discrete survival function adjusting for age, sex and calendar year. Adjustment for smoking status was explored in a subgroup of 4023 with smoking information available. Results: Cumulative organic dust exposure was inversely associated with COPD (adjusted rate ratios (RRadj (95% CIs) of 0.90 (0.82 to 0.99), 0.76 (0.69 to 0.84) and 0.52 (0.47 to 0.58) for intermediate-low, intermediate-high and high exposure quartiles, respectively, compared with the lowest exposure quartile). Lagging exposure 10 years was not consistently suggestive of an association between cumulative exposure and COPD; RRadj (95% CI): 1.05 (0.94 to 1.16), 0.92 (0.83 to 1.02) and 0.63 (0.56 to 0.70). Additional stratification by duration of employment showed no clear association between organic dust exposure and COPD except for the longer exposed (15–40 years) where an inverse association was indicated. Subgroup analyses showed that smoking had no impact on exposure-response estimates. Conclusions: Our findings show no increased risk of COPD with increasing occupational exposure to organic dust in the farming or wood industry. Potential residual confounding by smoking can, however, not be ruled out.